Character Association and Path Analysis in Buffel Grass - Mishra, U S; Katiyar, D S; Kumar, Ashok (Annals of Arid Zone, 2016)
Correlation studies in buffel grass revealed that selection for plant height, tiller number/plant, leaf number/tiller and leaf length will be effective for increasing green matter while dry matter is related more to plant height and tiller number and less with leaf characters. Path coefficient analysis revealed that plants with more height and tiller number will improve dry matter while good height, high leaf number and leaf length will be desirable attributes for the improvement of green matter.